How did the company respond to reviews on twitter? Es teh indonesia' case - Agatha, Gabrielle; Susilo, Daniel; Juliadi, Rismi (Jurnal Studi Komunikasi, 2023)
These days, consumers can easily and quickly express their opinions through social media. This has a big impact and need to be responded wisely by the company. At the end of September 2022, PT Esteh Indonesia Makmur issue a subpoena to the account @ghandoyy due to the use of language and criticism which was considered misleading. Researchers want to see the analysis of social networks and network discourse formed through the concept of issue management and reputation on Twitter using applications such as Netlytic, Gephi, Brand24, DNA, and Visone. The network formed shows that there are many actors and discourses involved. Several clusters form a relationship and a higher degree, in which there are dominant actors who are connected to each other. Future research may shed lighter and more expected to analyze deeper to discuss network analysis using different tools and social media.